Synergistic Fluoride Adsorption by Composite Adsorbents Synthesized From Different Types of Materials—A Review - Wei, Yifei; Wang, Li; Li, Hanbing; Yan, Wei; Feng, Jiangtao (Frontiers in Chemistry, 2022)
The reduction of fluoride concentrations in water is one of concerns. Adsorption is the most widely used technology for fluoride removal and the central to development of adsorption technology is the improvement of adsorbents. This review classifies the typical fluoride removal adsorbents into four types: metal oxides/hydroxides, biopolymer, carbon-based and other adsorbents. The exploitation of new materials and the synthesis of composite materials are two ways of developing new adsorbents. In comparison to the discovery of novel adsorbents for fluoride adsorption, research into the composite synthesis of different types of conventional adsorbents has proliferated in recent years. And the traditional adsorbents used earliest, metal oxides, can act as active centres in a wide range of applications for modifying and compounding with other types of adsorbents. This paper emphasizes reviewing the research on fluoride removal by composite adsorbents synthesized from metal modified different types of materials. Seven factors were compared in terms of material characterization, initial fluoride concentration, adsorbent dose, pH, temperature, reaction time and maximum adsorption capacity. The modification of composite adsorbents is facile and the synergistic effect of the different types of adsorbents significantly improves fluoride adsorption capacity. Metal composite adsorbents are synthesized by facile co-precipitation, hydrothermal or impregnation modification methods. The adsorption mechanisms involve electrostatic attraction, ion exchange, complexation and hydrogen bonding. The fluoride adsorption capacity of composite adsorbents has generally improved, indicating most modifications are successful and have application prospects. However, to achieve significant breakthroughs in practical applications, numerous issues such as cost, separation/regeneration performance, and safety still need to be considered.